CHARACTER DEVELOPMENT OF SANTRI AT DARUL AMANAH ISLAMIC BOARDING SCHOOL, KENDAL: A QUALITATIVE STUDY ON THE ROLES OF THE KYAI, CURRICULUM, AND DORMITORY ENVIRONMENT - Fatwa, Muhammad (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study examines the character development of santri at Darul Amanah Islamic Boarding School, Kendal, by focusing on the roles of the kyai, curriculum, and dormitory environment as the core elements in value internalization. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the kyai serves as a central figure who provides moral exemplification, spiritual guidance, and continuous supervision. The pesantren curriculum integrates religious and general subjects with habituation practices, language strengthening, and extracurricular programs that foster morality, discipline, and independence. The dormitory environment functions as a social space in which students apply values daily through peer interaction, structured routines, collective activities, and social control mechanisms. The integration of these three dimensions creates a comprehensive and sustainable character-building system. The study highlights that effective character development depends not only on formal curriculum design but also on the exemplary leadership of the kyai and the cultural environment of the dormitory that consistently supports the practical and continuous internalization of values. Penelitian ini bertujuan untuk menganalisis pembinaan karakter santri di Pondok Pesantren Darul Amanah Kendal melalui peran kyai, kurikulum, dan lingkungan asrama sebagai tiga elemen utama dalam proses internalisasi nilai. Menggunakan pendekatan kualitatif dengan desain studi kasus, data diperoleh melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil penelitian menunjukkan bahwa kyai berperan sebagai figur sentral yang memberikan keteladanan, arahan spiritual, serta penguatan nilai melalui nasihat dan pengawasan rutin. Kurikulum pesantren mengintegrasikan ilmu agama dan umum dengan pendekatan pembiasaan, penguatan bahasa, serta kegiatan ekstrakurikuler yang mendukung pembentukan akhlak, kemandirian, dan kedisiplinan. Lingkungan asrama berfungsi sebagai ruang sosial yang memungkinkan santri menerapkan nilai-nilai dalam kehidupan sehari-hari melalui interaksi, kegiatan bersama, pengaturan jadwal, dan mekanisme kontrol sosial. Integrasi ketiga komponen tersebut menciptakan sistem pembinaan karakter yang komprehensif dan berkesinambungan. Temuan ini menegaskan bahwa keberhasilan pembinaan karakter tidak hanya bergantung pada kurikulum formal, tetapi juga pada keteladanan kyai dan kultur asrama yang mendukung internalisasi nilai secara praktis dan berkelanjutan.